Development, Characterization, and In Vitro Biological Performance of Fluconazole-Loaded Microemulsions for the Topical Treatment of Cutaneous Leishmaniasis. (12th January 2015) - Oliveira, Marcela Brito; Calixto, Giovana; Graminha, Márcia; Cerecetto, Hugo; González, Mercedes; Chorilli, Marlus
Abstract : Cutaneous leishmaniasis (CL) is a resistant form of leishmaniasis that is caused by a parasite belonging to the genus Leishmania . FLU-loaded microemulsions (MEs) were developed by phase diagram for topical administration of fluconazole (FLU) as prominent alternative to combat CL. Three MEs called F1, F2, and F3 (F1—60% 50 M phosphate buffer at pH 7.4 (PB) as aqueous phase, 10% cholesterol (CHO) as oil phase, and 30% soy phosphatidylcholine/oil polyoxyl-60 hydrogenated castor oil/sodium oleate (3/8/6) (S) as surfactant; F2—50% PB, 10% CHO, and 40% S; F3—40% PB, 10% CHO, and 50 % S) were characterized by droplet size analysis, zeta potential analysis, X-ray diffraction, continuous flow, texture profile analysis, and in vitro bioadhesion. MEs presented pseudoplastic flow and thixotropy was dependent on surfactant concentration. Droplet size was not affected by FLU. FLU-loaded MEs improved the FLU safety profile that was evaluated using red cell haemolysis and in vitro cytotoxicity assays with J-774 mouse macrophages. FLU-unloaded MEs did not exhibit leishmanicidal activity that was performed using MTT colourimetric assays; however, FLU-loaded MEs exhibited activity. Therefore, these MEs have potential to modulate FLU action, being a promising platform for drug delivery systems to treat CL.